Aplicaçáo de modelos hidrológicos para avaliação de reservatórios de retençáo e detençáo combinados á obra de recuperaçáo do canal de macrodrenagem no controle de cheias em uma bacia hidrográfica urbanizada - Moruzzi, Rodrigo Braga [UNESP]; Lupinacci Da Cunha, Cenira Maria [UNESP]; De Oliveira, Jefferson Nascimento [UNESP] (My University, 2009)
The aim of this paper was to evaluate the effect of retention and detention reservoirs along with the regulation in channel flow upgrade on flood for an urban watershed located at Rio Claro, SP. For this purpose, modeling and simulation techniques were applied for runoff determination and its propagation in channel. The Soil Conservation Service - SCS hydrologic model as well as Pulz and non-linear Muskingum-Cunge model were used. The software IPHS1 was applied on simulations. The results pointed out that the combination of retention increasing and detention reservoir implementation (120,000 m3, corresponding to 1.5% of the watershed area) with the streamflow upgrade (n decreasing from 0,04 to 0,02) can minimize the flood on the investigated Servidão watershed. Further, after the proposed intervention, the flood was eliminated for the investigated times of recurrence: 5, 20, 50 and 100 years. The prognostic indicated that the available area occupation had a minor effect on flow increasing due to the observed high urbanization.
Use of hydrological models to evaluate the detention and retention reservoirs combined with the recuperation of the macro drainage channel in the flood control of an urbanized watershed
Keywords: Flood control; Hydrologic simulation; Muskingum-Cunge model; Pulz model; Retention and detention reservoirs; SCS model